Peningkatan Kemandirian Masyarakat dalam Pencegahan Penyakit Tidak Menular di Wilayah Puskesmas Wagir Kabupaten Malang - Ka’arayeno, Arie Jefry; Putri, Santy Irene; Widiyanto, Aris; Cahyaningrum, Ika; Cita, Erick Endra; Susmini, Susmini; Dewi, Novita; Luthfiyana, Nurul Ulya; Anasulfalah, Hakim; Hanif, Ihsan; D, Rizki Aqsyari (LPPM Universitas Timor, 2025)
Poorly controlled diabetes mellitus is a major cause of blindness, heart attack, amputation, stroke, kidney failure, and impotence. Hypertension is a major risk factor for cardiovascular disease and stroke. The prevalence of diabetes and hypertension is increasing globally. There is strong evidence from clinical trials that lifestyle modification and education can minimize the risk of diabetes and high blood pressure, as well as preventive measures that can reduce morbidity and mortality. Based on a study carried out by the team before the activity was held, information was obtained that the majority of pre-elderly and elderly residents had never had a health check-up. The aim to be achieved in this activity is to provide health education through checking blood pressure and blood sugar as well as providing counseling to pre-elderly and elderly groups. This program was held on November 11, 2023 at the Pandanrejo Village Hall, Wagir District, Malang Regency with a total of 50 participants. The methods used to solve partner problems are health checks and counseling. After carrying out the activities, pre-elderly and elderly residents can find out their blood pressure and blood sugar levels and understand well about healthcare efforts.